Apoptotic Cell-Derived Extracellular Vesicles: More Than Just Debris - Caruso, Sarah; Poon, Ivan K. H. (Frontiers in Immunology, 2018)
The many functions of extracellular vesicles (EVs) like exosomes and microvesicles released from healthy cells have been well characterised, particularly in relation to their roles in immune modulation. Apoptotic bodies (ApoBDs), a major class of EV released as a product of apoptotic cell disassembly, and other types of EVs released from dying cells are also becoming recognised as key players in this emerging field. There is now increasing evidence to suggest that EVs produced during apoptosis have important immune regulatory roles, a concept relevant across different disease settings including autoimmunity, cancer and infection. Therefore, this review focuses on how the formation of EVs during apoptosis could be a key mechanism of immune modulation by dying cells.